The Impact of Islamic Bank Mergers on Work Culture and Customer Service Quality: A Case Study of Bank Syariah Indonesia (BSI) in Mandailing Natal - Amelia Sri Ningsih; Muhammad Arif; Wahyu Syarvina (Jurnal Investasi Islam, 2026)
The merger of three state-owned Islamic banks into Bank Syariah Indonesia (BSI) is a strategic move to strengthen the national Islamic banking industry. However, previous studies have largely focused on financial performance and competitiveness, while research on the merger’s impact on employee work culture and customer service quality at the branch level remains limited, particularly in Mandailing Natal Regency. This study aims to analyze the impact of the BSI merger on employee work culture and customer service quality at BSI Mandailing Natal. This study employs a qualitative approach using the case study method. Data were collected through in-depth interviews and observations from 5 informants comprising BSI employees and customers selected using purposive sampling. The results of the study indicate that the BSI merger has driven changes in work culture toward a more dynamic, fast-paced, integrated, and digitally oriented environment. Employees are required to enhance their adaptability, product knowledge, and service competencies. From a service perspective, the merger has improved access to services through the development of BSI Mobile, the expansion of the ATM network, and the simplification of digital transactions. Nevertheless, during the transition period, challenges were still encountered, including account migration processes, digital system disruptions, and limited access to services for some customers. This study concludes that the BSI merger has had a impact on the transformation of work culture and the improvement of customer service quality. These findings contribute to the development of research on post-merger organizational integration in Islamic banking and provide insights for BSI management in strengthening digital transformation strategies and enhancing service quality.